2020
DOI: 10.3102/0002831220946309
|View full text |Cite
|
Sign up to set email alerts
|

Competing for Bachelor’s Degrees: Are Community Colleges Cutting Into the Market Share of 4-Year Institutions?

Abstract: To address local workforce needs and expand access to affordable bachelor’s degrees, some states allow community colleges to offer bachelor’s degree programs. Despite concerns that community college baccalaureate (CCB) programs will duplicate efforts and cut into the market share of nearby 4-year institutions, extant literature has yet to examine the impact of CCB adoption on bachelor’s degree program enrollment and bachelor’s degree production at 4-year institutions. Using program-level data, our findings sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Recent quasi-experimental analysis of duplicative programming across baccalaureate education in Florida provide further insight. After accounting for institution and county-level characteristics, Kramer et al (2020) estimated the impact of CCB adoption on bachelor's degree enrollment across the state's 4-year institutions. The authors found a significant 12.5% decrease in bachelor's degree enrollment at 4-year institutions in counties with community colleges offering CCBs.…”
Section: Student Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent quasi-experimental analysis of duplicative programming across baccalaureate education in Florida provide further insight. After accounting for institution and county-level characteristics, Kramer et al (2020) estimated the impact of CCB adoption on bachelor's degree enrollment across the state's 4-year institutions. The authors found a significant 12.5% decrease in bachelor's degree enrollment at 4-year institutions in counties with community colleges offering CCBs.…”
Section: Student Accessmentioning
confidence: 99%
“…However, this effect was attributed to decreases in enrollments at for‐profit institutions, as examination of the effects by sector showed no significant impact at public and private, not‐for‐profit 4‐year institutions. Moreover, the authors describe this negative effect as a positive outcome, as for‐profits tend to cost more than community colleges and boast worse outcomes than comparable institutions (Kramer et al., 2020).…”
Section: What We Knowmentioning
confidence: 99%
“…Without faculty support, expertise, commitment, and collaboration, reform efforts and changes are unlikely to succeed (Klempin & Karp, 2018; Yeager, 2017). Among the various curricular developments on the rise at community colleges is the community college baccalaureate (Bragg et al, 2021; Kramer et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In May 2021, Arizona became the 24th state to authorize community college baccalaureates (CCBs; Weissman, 2021). The rise in CCB programs is reflected in the number of bachelor’s degrees conferred at public community colleges (Kramer et al, 2021). Recent calculations by Kramer et al (2021) show an increase from 525 bachelor’s degrees conferred at public community colleges in 2001 to 13,283 in 2018.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation